School Expenditures and Post-Schooling Earnings: Evidence from High School and Beyond - Grogger, Jeff (The Review of Economics and Statistics, 1996)
Studies based on inputs measured at the state level generally report that school expenditures have substantial effects on students' adult wages, whereas studies based on less aggregated measures report small effects. The author uses wage data from High School and Beyond to analyze this discrepancy, and to estimate the effect of school expenditures on students' post-schooling earnings. The author finds that the discrepancy in the literature stems mostly from two factors: measurement error in district-level expenditures and omitted state effects in the earnings regression. The author also finds that the effect of school expenditures on earnings is significant but small. A 10% increase in school spending would increase students' adult wages by only 0.68%. Copyright 1996 by MIT Press.